Single-Cell mRNA Sequencing of Murine and Human Alopecia Areata Identifies Immune Cell Profiles Predictive of Human Disease State. (28th October 2020) - Borcherding, Nicholas; Crotts, Sydney; Ortolan, Luana; Bormann, Nicholas; Jabbari, Ali
Abstract: Alopecia areata (AA) is one of the most common autoimmune conditions, presenting initially with loss of hair without overt skin changes. The unremarkable appearance of the skin surface contrasts with the complex immune activity occurring at the hair follicle. AA pathogenesis is due to the loss of immune privilege of the hair follicle leading to autoimmune attack. Although the literature has focused on CD8 + T cells, vital roles for CD4 + T cells and antigen-presenting cells have been suggested. Here, we use single-cell mRNA sequencing to reveal distinct expression profiles of immune cells in AA. We found clonal expansions of both CD4 + and CD8 + T cells, with shared clonotypes across varied transcriptional states. Demonstrating distinct gene and clonotypic variations, AA murine data were used to generate highly predictive models of human AA disease. In order to corroborate the results, single-cell sequencing of T cells in human AA recapitulated the clonotypic findings and the gene expression of the predictive models. Taken together, this work demonstrates the unique transcriptomic environment of AA skin, not just limited to CD8 + T cells. This work also represents the first single-cell sequencing for the autoimmune condition AA.